STRATEGI PEMBELAJARAN BAHASA ARAB DALAM PENCAPAIAN MAHARAH AL-QIRAAH PRODI MANAJEMEN PENDIDIKAN ISLAM FAKULTAS TARBIYAH DAN KEGURUAN INSTITUT PARAHIKMA INDONESIA (IPI) - Mansyur Mansyur (EKSPOSE, 2017)
The main problem of this research is how the strategy of learning Arabic in the achievement of al-qira'ah in the Department of Management of Islamic Education Institute Parahikma Indonesia (IPI). The results of this study show that the strategy of learning Arabic in the achievement of Maharah al-Qira'ah to the Students of the Department of Management of Islamic Education Institute of Parahikma Indonesia (IPI) is done by reading the Arabic books, interpreting and rewriting, giving the reading without syakal and discussed, recognize words and sentences and then translate, compose own sentences with a vocabulary that is considered easy.